Sodium butyrate attenuate hyperglycemia-induced inflammatory response and renal injury in diabetic mice - Yan Man; Zhang Yan-Yan; Xi Yue; Ding Long-Kun; Sun Chang; Qu Li-Juan; Qian Xin; Xu Jing-Wen; Sun Wen; Wu Liang (Acta Pharmaceutica)
The activation of the monocyte-macrophage system and the damage to the renal and pancreatic tissue are common complications in patients with diabetes induced by hyper-glycemia. This study aimed to evaluate the effect and mechanism of butyrate (NaB), a metabolite of intestinal flora, on inhibiting the inflammatory response of human monocyte-macrophages (THP-1 cells) induced by high glucose and the damage of pancreatic and renal tissue in diabetic mice. The results showed that high concentration glucose significantly up-regulated the expressions of IL-1β, TNF-α, and NLRP3 in THP-1 cells and mouse spleen, and that NaB could inhibit the overexpression of those genes. The abundance of Beclin-1, LC3B and reactive oxygen species (ROS) in THP-1 cells is increased due to the high glucose concentration, and NaB can inhibit the genes responsible for upregulating the expression. In diabetic mice, vacuolar degeneration of renal tubules was observed. Then we observed that some of the epithelial cells of the renal tubules were exfoliated and some formed tubules. NaB could alleviate these pathological lesions, but NaB cannot alleviate pancreatic injury. Our results indicated that NaB could be used for the prevention and adjuvant treatment of diabetic kidney injury.